IDENTIFYING CANAL SURFACES IN E4 : CHARACTERIZATION OF A SPECIAL CASE - Gurses, Nurten (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2020)
This study, develops a way for representation of canal surfaces in 4-dimensional Euclidean space E-4. It examines the fundamental forms, Gaussian and mean curvature for a special type canal surface. Moreover, the conditions of both Weingarten and linear Weingarten canal surfaces are given for this new special type. Finally, the graphs of the projections of the canal surfaces using different radius functions in E-4 are presented.
Keywords: canal surface; tube surface; Weingarten surface; Gaussian curvature; mean curvature; CURVES; CURVATURES; LINES; Science & Technology - Other Topics